Іван Лисяк-Рудницький про українське націєтворення в європейському контексті - Діптан, І. (Сiверянський літопис, 2020)
Об'єктом дослідження є наукова спадщина українського інтелектуала середини та другої половини ХХ ст., чия фахова діяльність розгорталася на еміграції, Івана Лисяка-Рудницького; предметом – історико-політичні студії вченого, присвячені ґенезі та еволюції національної суспільно-політичної думки в новітню добу.
Мета історіографічної розвідки полягає у висвітленні поглядів історика на ключові, дискусійні й на сьогодні, проблеми українського націєтворення як специфічні його риси, так і ті, що притаманні формуванню європейських націоспільнот.
Методологія пошуку ґрунтується на засадах об'єктивізму та історизму; його наукова значимість зумовлена недостатнім рівнем розробки теми. Висновки. У результаті прочитання відповідних праць І. Лисяка-Рудницького авторка доходить
загального висновку про безперечну цінність наукового доробку мислителя, необхідність вивчення його візії національної минувшини в європейському контексті,
вартісність аналітики, проникливість суджень і застережень, актуальних для
успішної розбудови вже втретє відродженої України. По-перше, у розумінні дослідника поняття «народ» і «нація» – співвідносні, проте не тотожні: «народ»
– одиниця етнічна; натомість «нація» – явище політичне, оскільки так він характеризує спільноту людей, що самоусвідомила себе до потреби власного державного буття. По-друге, І. Лисяк-Рудницький підкреслює специфіку українського
націєтворчого процесу – наявність бездержавних позанаціональних періодів: перший – після Любліна 1569 р. і до постання в 1648 р. Козацької держави; другий – із ліквідацією в другій половині 80-х рр. XVIII ст. козацької автономії і до УНР часів
Центральної Ради та Директорії, Гетьманату П. Скоропадського; третій – після
поразки Української революції 1917–1921 рр. По-третє, розмірковуючи над таким явищем, як «національний характер», історик акцентує на винятковому значенні у формуванні його перебування України «між «Сходом» і «Заходом». Учений підкреслює органічну приналежність України до європейської спільноти народів (як основний аргумент – спільна культурна та політична спадщина). По-четверте,
вагоме місце в політичних студіях І. Лисяка-Рудницького займає проблематика
українського націоналізму (від диференціації поняття, сутності, витоків – до його трансформації, значення). The purpose of our historiographical discourse is to represent Ivan Lysiak-Rudnytsky
views on the key problems of Ukrainian nation-statement using the basis of his works.
Analysis of the relevant works of the scientist gives a number of conclusions. First, in
the researcher's understanding, the concepts of «people» and «nation» arerelative, but
not identical. «People» is an ethnic unit; instead, «nation» is a political phenomenon, a
community of people who are self-aware of the need for their own state existence. According
to the scientist, the nation in Europe is not a product of an exclusively modernage; it
appearsin 10th–11th centuries; the second half of the 15th and early 16th centuries is the
period of the establishment of European monarchies; the end of the 18th–19th centuries
is the creation of modern nations. Secondly, the historian chronologizes the completion of
the ethnogenesis of Ukrainians, mainly in the middle of the first millennium AD, and sees
the beginning of the formation of the Ukrainian nationin Kyivan Rus; its crystallization –
in Principality of Galicia–Volhynia and in the Grand Duchy of Lithuania. Thirdy, Ivan Lysiak-Rudnytsky emphasizes the specifics of the Ukrainian nation-statement process. It is the existence of stateless non-national periods: the first one starts
from the Union of Lublin in 1569 till rise of the Cossack state in 1648; the second one is
from the liquidation of the Cossack autonomy and to Ukrainian National Republic period
of the Central Council and Directory, Hetmanate of Pavlo Skoropadsky in the second
half of the 80's of the 18th century; the third one starts with the defeat of the Ukrainian
revolution in 1917–1921 (until 1991; the historian wasn’t alive to see the third revival
of the Ukrainian nation-state). Using the concepts of «historical» / «non-historical» nations,
the scientist emphasizes that the decisive factor in the viability of a nation (even
in the event of the loss of its own state) is the presence (preservation) of the leading
stratum – the political people. Instead, the Ukrainian elite was «polonized» in the Polish-
Lithuanian Commonwealth, «russified» in the Russian and Soviet empires (in the latter,
the Ukrainian peasantry and intelligentsia were subject to physical destruction).
Fourth, reflecting on such a phenomenon as «national temper», the historian
emphasizes the exceptionalim portance in shapinghis stay in Ukraine between «East»
and «West». The scientis temphasizes the organic belonging of Ukraine to the European
community of nations (the common cultural and political heritageis the mainargument).
Fifth, an important place in the political studies of Ivan Lysiak-Rudnytsky is given
to the problems of Ukrainian nationalism (from the differentiation of the concept, essence,
origins to its transformation and meaning). Considering «nationalism» in a narrowmeaning
(as a political movement –«integral nationalism»), the historian defines it
as a socio-political reaction of Ukrainians to the results of World War I and the defeat of
the Ukrainian Revolution of 1917–1921. Sixth, given the next Russian imperial expansion (undeclared, but real war, since
March 2014), the following warning of Ivan Lysiak-Rudnytsky: «including its dangerous geographical position, Ukraine only has a chance to survive politically when Ukrainians will be able to unite against the external threat and oppression».